The effects of personality traits and psychological well-being among Iranian adolescent migrants in Kuala-Lumpur, Malaysia - Mobarakeh, Mohammad Reza Vakili; Juhari, Rumaya; Yaacob, Siti Nor; Redzuan, Marof; Mobarakeh, Shakiba Iranpour (International Organization Of Scientific Research, 2015)
The purpose of this study was to determine the relationships between personality traits and psychological well-being among Iranian adolescent migrants in Kuala Lumpur, Malaysia. The participants were 300 high schools adolescents who comprise(143 males,and 157 females)in the age range of 13 to be 16 years old. The instrument used to measurement personality traits was Five Factor Inventory (FFI-NEO) Iranian version by Costa and McCrae, (1992)and psychological well-being Scale by Ryff, and keys,(1995).The results from the study showed that there was negative statistical significant relationship between neuroticism trait and adolescent's psychological well-being, while extroversion and agreeableness traits have positive correlation with psychological well-being. However, the results also indicated that openness to experience and conscientiousness traits do not have statistical significance relationships with psychological well-being.